Pertanggungjawaban Pelaku Tindak Pidana Perjudian yang di Lakukan di Tempat Umum - Indrahayu M Umar Gazali; Raodiah (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to determine how the criminal law regulates gambling crimes in Indonesia and how criminal liability is imposed on perpetrators of gambling in public places. The method used in this writing is to use normative legal research (juridical normative) which is carried out with library research. This study was conducted using secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. The results of this study indicate that the Crime of Gambling is regulated in Article 303 of the Criminal Code, (I) With a maximum imprisonment of 10 (ten) years or a maximum fine of Rp. 25,000,000, - (twenty five million rupiah), anyone who does not have the right to do so: intentionally does as a business, offers or provides an opportunity to gamble or intentionally participates in such a business; intentionally offering or giving the public the opportunity to gamble or intentionally participating in such an endeavor without regard to whether the use of the opportunity is conditional on a condition or on knowledge of a method or not; participating in gambling as an endeavor. (2) If the person guilty of committing the crime in his work, then his right to do that work can be revoked. (3) What is meant by gambling is every game that generally depends on the possibility of obtaining the profit on the factor of chance, also if the opportunity becomes greater with higher training or with higher dexterity of the player. Included in the definition of gambling is also betting or the results of matches or other games, which are not held between those who participate in the game themselves, as well as every other betting.